Attitude Control of Small Scientific Satellite Using Geomagnetism - Sung-Koo Bae; Jae-Ho Seok; Kyu-Hong Choi (Journal of Astronomy and Space Sciences, 1991)
Geomagnetism was used to control the attitude of the small scientific satellite at low altitude in sun-synchronous orbit. First, we analyzed the telemetry data. The rotation state of the satellite can be known from the magnitude and variations of the magnetic field which is measured from the 3 axis magnetometer. In axisymmetric case, it is possible to control the attitude of the satellite by changing the rotation velocity of each 3 axis. The algorithm and the program were developed to calculate the supply time of the current operating the magnetorquer. This attitude control can be applied when the satellite is in tumbling motion and after passive control is attained by the Gravity gradient boom.